2019
DOI: 10.1073/pnas.1900275116
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic amino acids bind to and stabilize prebiotic fatty acid membranes

Abstract: The membranes of the first protocells on the early Earth were likely self-assembled from fatty acids. A major challenge in understanding how protocells could have arisen and withstood changes in their environment is that fatty acid membranes are unstable in solutions containing high concentrations of salt (such as would have been prevalent in early oceans) or divalent cations (which would have been required for RNA catalysis). To test whether the inclusion of amino acids addresses this problem, we coupled dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 41 publications
(68 reference statements)
5
84
0
1
Order By: Relevance
“…Studies merging the lipid world with others are pioneers. The requirement for compartmentalization to keep genomic molecules and their products spatially together, as well as to allow for vectorial (bio)chemistry, suggests that the potential of lipids and other amphiphilic structures to self-assemble into micelles and bilayer vesicles within an aqueous phase constituted a critical step in the emergence of life [57,126,127]. Vesicles were thought to be stable only in salt-poor aqueous environments, such as surficial freshwater ponds or hydrothermal springs, but recent work showed that these become much more resilient to extreme salinity and pH if they are composed of mixtures of amphiphiles [128], a feature which better reflects the naturally messy aspect of prebiotic chemistry.…”
Section: On the Right Track? Looking At The Past Decadementioning
confidence: 99%
“…Studies merging the lipid world with others are pioneers. The requirement for compartmentalization to keep genomic molecules and their products spatially together, as well as to allow for vectorial (bio)chemistry, suggests that the potential of lipids and other amphiphilic structures to self-assemble into micelles and bilayer vesicles within an aqueous phase constituted a critical step in the emergence of life [57,126,127]. Vesicles were thought to be stable only in salt-poor aqueous environments, such as surficial freshwater ponds or hydrothermal springs, but recent work showed that these become much more resilient to extreme salinity and pH if they are composed of mixtures of amphiphiles [128], a feature which better reflects the naturally messy aspect of prebiotic chemistry.…”
Section: On the Right Track? Looking At The Past Decadementioning
confidence: 99%
“…A difficulty for an origin of life in saline lakes is that high salt concentrations tend to destabilize lipid vesicles (56) and inhibit RNA oligimerization (57), but these issues are potentially resolvable. For example, lipid vesicles can stabilize in high-salt environments by binding to nucleotides and/or amino acids (58,59). Given that concentrated prebiotic reagents and wet/dry cycles often used in the laboratory imply saline environments, more research is needed on prebiotic chemistry in salty solutions.…”
Section: Implications For Prebiotic Chemistrymentioning
confidence: 99%
“…For instance, Groen et al (2012) reported that polycyclic aromatic hydrocarbons (PAHs), components of meteoritic organics, have a stabilizing effect on fatty acid membranes, similar to the effect of another polycyclic compound-cholesterol-on membranes today. Black et al (2013) showed that adenine has a stabilizing effect on fatty acid membranes, and Cornell et al (2019) observed similar effects of certain amino acids. For an origin of life on a terrestrial world possessing liquid water, it is the exposed land surfaces that would provide the richest array of compounds, environments, cycling systems, and the greatest range of energy sources (Deamer and Weber, 2010).…”
mentioning
confidence: 94%
“…This binding has been shown to stabilize the membrane against stresses (Black et al, 2013;Mayer et al, 2018), and would also enable sets of polymers to become more crowded on the two-dimensional surface and interact more easily. Recently, Cornell et al (2019) proposed that this colocalization sets up ''a positive feedback loop in which amino acids bind to self-assembled fatty acid membranes, resulting in membrane stabilization and leading to more binding. [and that] high local concentrations of molecular building blocks at the surface of fatty acid membranes may have aided the eventual formation of proteins.''…”
mentioning
confidence: 99%